THE EFFECT OF PICTURE MEDIA ON ISLAMIC RELIGIOUS EDUCATION LEARNING ACHIEVEMENTS - Aldi Alfariz, Ruwaida, Rahmi Syafriyeti (STAI Syaichona Moh. Cholil Bangkalan, 2025)
Children are a gift from God, children have a certain age limit, the next generation of the nation, unique characteristics, have a special growth and development pattern according to their growth and development levels which are very fundamental to life, so children with good quality are needed in order to achieve a quality future for the nation, good children must be ensured that their growth and development are also good. The process of child growth and development can take place naturally, but the process is very dependent on parents. This means that parents have an important role in realizing quality resources. As for character, it is an innate trait that is usually inherited from both parents, so character can sometimes make people around them happy, but there are also some that make it difficult for parents to overcome it